Bound‐based spectrum allocation for cooperative positioning. Issue 1 (25th October 2012) - Raulefs, R.; Zhang, S.; Mensing, C.; Dammann, Armin; Plass, Simon; Fazel, Khaled
ABSTRACT This paper discusses the performance of distributed and centralised cooperative positioning system for multiple mobile terminals. A cooperative positioning system uses ranging between base stations and mobile terminals, and in addition exploits the links between the mobile terminals as well. However, the number of links in an all‐to‐all connected setup increases quadratically with the number of nodes. Our goal is to schedule the access for the available resources (used bandwidth) to track the nodes of a dynamic system. Therefore, it is essential to reason if the different links between the mobile terminals are useful. The reasoning assists in allocating resources properly. We investigate distributed algorithms that act based on the Cramér–Rao Lower Bound. We use as benchmark a centralised and much more complex algorithm that requires all link information and we ignore any latency aspects. The results show that our distributed algorithm using limited information performs well. Copyright © 2012 John Wiley & Sons, Ltd.